The Effect of the Use of Gadgets on PAI Learning Outcomes at SDN 2 Dwijaya, Musi Rawas Regency - Widiyanti, Nyandi; Romelah, Romelah; Mardiana, Dina (ISTAWA, 2024)
This study aims to analyze the effect of the use of gadgets on the learning outcomes of Islamic Religious Education (PAI) in elementary school students. In the growing digital era, gadgets have become an almost inseparable tool in everyday life, including in learning activities. The use of gadgets can have both positive and negative impacts on students' learning process. The positive impacts include wider access to learning materials, interactive educational applications, and ease of communication and collaboration. However, uncontrolled use of devices also has the potential to reduce students' concentration and focus, thus affecting their understanding of PAI materials. This study uses a quantitative approach by taking a sample of all students in grades IV and V of SDN 2 Dwijaya Musi Rawas to objectively measure the relationship between the variables of device use and PAI learning outcomes, data analysis is carried out through reliability and validity tests so that accountable data is obtained. As well as descriptive analysis to measure the extent to which the use of gadgets affects PAI learning outcomes. T test was also conducted which aims to measure whether or not there is an influence of the use of gadgets on PAI learning outcomes. The results showed that the proper use of gadgets can increase students' motivation and understanding of PAI materials, but excessive and undirected use actually reduces learning outcomes. Therefore, an effective strategy is needed in utilizing devices as a learning medium that supports optimal learning outcomes